HAUZES OF MEDIEVAL BUKHARA - ARTERIES OF LIFE - Nematjonovna, Sadikova Sitora-bonu; Bahriddinovna, Hafiza Hafiza (International Journal of Psychosocial Rehabilitation, 2020)
This article is devoted to the history of the development of the water supply system of Central Asian historical cities, using the example of Bukhara and Samarkand. The purpose of this article is to study the system of water tanks and irrigation ditches of medieval Bukhara, to identify its features that contributed to the evolution of simple natural water arteries - irrigation ditches and water reservoirs - houses into the town-planning, landscape infrastructure of the historical city. The article highlights the unique features of the traditional water supply of urban reservoirs - water tank and aryks (ditches) of Samarkand and Bukhara in the period of antiquity and the Middle Ages. The main aspects of the research that formed the basis of this article are how the ancient, original, ten-century-old water supply system of Bukhara and Samarkand was modified under the influence of the development of civilization; the role of clean running water sources - irrigation aryks (ditches) and water tanks in the conditions of the hot arid climate of the ancient cities of Samarkand and Bukhara through the centuries and today; the function and contribution of this water supply system to the development of tourism in the historical center of the aforementioned cities today. In order to study more deeply the issue of introducing water tanks into the architectural composition of medieval ensembles, their contribution to the development of the urban social structure and architecture, we studied the planning features of the medieval architectural monuments of Samarkand and Bukhara that have survived to this day. Thus, a number of features were identified in the architectural, planning and landscape solutions of historical ensembles. Based on a study of the literary sources of ancient Eastern authors and Soviet scholars, a field survey of some ditches and water tanks of Samarkand that have survived to this day, as well as diagrams and maps with designations of aryks and water tanks, forming a single water supply system for Samarkand and Bukhara, several conclusions have been made that meet the set at the beginning of the research questions. According to the findings of the study, the author put forward a number of proposals and recommendations aimed at reviving the original system of water tanks and aryks of Samarkand and Bukhara - as the historical architectural heritage of Uzbekistan.